2013
DOI: 10.1007/s11033-013-2803-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of SSR markers by next-generation sequencing of Korean landraces of chamoe (Cucumis melo var. makuwa)

Abstract: The oriental melon (Cucumis melo var. makuwa), called 'chamoe' in Korean, is a popular fruit crop cultivated mainly in Asia and a high-market value crop in Korea. To provide molecular breeding resources for chamoe, we developed and characterized genomic SSR markers from the preliminary Illumina read assemblies of Gotgam chamoe (one of the major landraces; KM) and SW3 (the breeding parent). Mononucleotide motifs were the most abundant type of markers, followed by di-, tri-, tetra-, and pentanucleotide motifs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…SSRs, or microsatellites, are repeating sequences of 1–6 nucleotides and are widely distributed in genomes [ 36 ]. They are easily identified in whole genome sequences and are used as molecular markers due to high interspecies polymorphism, locus-specific co-dominance, and high transferability [ 43 ]. We identified 272 and 287 SSRs in the cp genomes of A .…”
Section: Resultsmentioning
confidence: 99%
“…SSRs, or microsatellites, are repeating sequences of 1–6 nucleotides and are widely distributed in genomes [ 36 ]. They are easily identified in whole genome sequences and are used as molecular markers due to high interspecies polymorphism, locus-specific co-dominance, and high transferability [ 43 ]. We identified 272 and 287 SSRs in the cp genomes of A .…”
Section: Resultsmentioning
confidence: 99%
“…Aragão et al (2013) found an average of 2.41 alleles per marker for 17 genomic SSR markers in 38 melon accessions representing different botanical groups. Park et al (2013) reported seven genomic SSR markers to identify six oriental melon accessions. These markers only produced a total of 17 alleles with 2 to 3 alleles per marker.…”
Section: Resultsmentioning
confidence: 99%
“…SSRs or microsatellites are tandem repeat sequences consisting of 1-6 nt sequence motifs in prokaryotic and eukaryotic genomes [22,23]. We detected 183 and 178 SSRs in F. ussuriensis and F. cirrhosa cp genomes, respectively.…”
Section: Repeat Analysis In Two Fritillaria Chloroplast Genomesmentioning
confidence: 91%